2022
DOI: 10.30541/v40i2pp.135-147
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Energy Consumption and Energy Intensity Changes in Pakistan: An Application of Complete Decomposition Model

Abstract: Complete decomposition model has been employed in the present study to decompose the changes in energy consumption and energy intensity in Pakistan during 1960 to 1998. A general decomposition model raises a problem due to residual term. In some models the residual term is omitted, which causes a large estimation error, while in some models the residual term is regarded as an interaction that might create a puzzle for the analysis. A complete decomposition model is used here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Rather, this might be the result of a change in the pattern of energy consumption, moving from more energy-intensive sub-sectors to less energy-intensive sub-sectors. These results are consistent with Alam and Butt (2001). On the other hand, the structural effect indicates that the structure of the economy changes, such that, society is more prone to energy consumption.…”
Section: Results Of the Logarithmic Mean Divisia Index (Lmdi) Approachsupporting
confidence: 93%
See 1 more Smart Citation
“…Rather, this might be the result of a change in the pattern of energy consumption, moving from more energy-intensive sub-sectors to less energy-intensive sub-sectors. These results are consistent with Alam and Butt (2001). On the other hand, the structural effect indicates that the structure of the economy changes, such that, society is more prone to energy consumption.…”
Section: Results Of the Logarithmic Mean Divisia Index (Lmdi) Approachsupporting
confidence: 93%
“…A review of the literature provides only one study on this topic regarding Pakistan, with many limitations. Alam and Butt (2001) evaluated the intensity and structural effects in the energy consumption of the agricultural sector. They found that structural changes are the main reason behind the rising energy intensity over time.…”
Section: Review Of Literature On Energy MIX and Intensitymentioning
confidence: 99%
“…Alam and Butt (2002) The current literature also includes numerous studies that have highlighted the extent of the relationship between economic growth and energy consumption by incorporating a number of control variables, such as financial development and urbanisation (Shahbaz and Lean, 2012;Islam et al, 2013;Menegaki and Ozturk, 2013). Similarly, the study by Alam et al (2007) provides evidence that population growth, economic development and urbanisation are the principal forces driving increases in energy demand, while these increases have a profound effect 3 Alam and Butt (2001) study the factor analysis for changes in energy intensity and energy consumption in Pakistan. Their results show that increases in aggregate energy intensity are due primarily to the structural effect, while increases in aggregate energy consumption are due to both the activity and the structural effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Study gives the evidence of long run relationship between electricity consumption and economic growth but inverse is not true. Alam and Butt (2001) investigation provided the evidence that structural changes also cause to change the share of various energy consumption variables. And increase in energy is because of increase in economic activity as well as structural changes.…”
Section: Literature Reviewmentioning
confidence: 99%